2002
DOI: 10.4049/jimmunol.168.2.763
|View full text |Cite
|
Sign up to set email alerts
|

Activated Human T Cells Accomplish MHC Class II Expression Through T Cell-Specific Occupation of Class II Transactivator Promoter III

Abstract: Activated human T cells express HLA-DR, HLA-DQ, and HLA-DP on their surface, but the regulation and functioning of MHC class II molecules in T lymphocytes are poorly understood. Because the MHC class II transactivator (CIITA) is essential for MHC class II expression, we have investigated transcriptional activation of CIITA in activated T cells. In this study, we show that in human activated CD4+ T cells, CIITA promoter III (CIITA-PIII) drives the expression of CIITA. The in vivo genomic footprint analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
130
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(138 citation statements)
references
References 51 publications
7
130
0
Order By: Relevance
“…By analogy with human T‐cell lymphoproliferative disorders, these features suggest that the normal counterpart of this neoplasm is a T cell that has completed its maturation, and is a single positive thymocyte or a mature peripheral T cell 23. Comparisons with human disease should be made cautiously, however, because expression of MHC class II is constitutive in dogs24, whereas it is a feature only of activated human T cells 25. This phenotype contrasts substantially with that described for T zone lymphoma, which expresses high levels of class II MHC, CD25, and CD21, all of which point to an activated phenotype (Seelig et al5).…”
Section: Discussionmentioning
confidence: 99%
“…By analogy with human T‐cell lymphoproliferative disorders, these features suggest that the normal counterpart of this neoplasm is a T cell that has completed its maturation, and is a single positive thymocyte or a mature peripheral T cell 23. Comparisons with human disease should be made cautiously, however, because expression of MHC class II is constitutive in dogs24, whereas it is a feature only of activated human T cells 25. This phenotype contrasts substantially with that described for T zone lymphoma, which expresses high levels of class II MHC, CD25, and CD21, all of which point to an activated phenotype (Seelig et al5).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the regulation of CIITA in different cell types and in response to different mediators will help uncover the signaling pathways involved and also the distinct functions that different CIITA types may play. Previous studies using mouse and human cell lines and primary cells have shown that PI is active in dendritic cells as well as in murine macrophages and microglia in response to IFN-␥; promoter III (PIII) is active in dendritic cells, T and B lymphocytes, as well as IFN-␥-activated cells; and promoter IV (PIV) is IFN-␥ responsive in murine and human macrophage and microglial cell lines as well as in non-bone marrowderived cells such as fibroblast, endothelial, and epithelial cells and cell lines, and astrocytes, and is also responsible for CIITA expression in murine cortical thymic epithelial cells (14,15,(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…However, candidate intermediates can be predicted based on what is known of GM-CSF signaling and CIITA promoter regulation. The cis regions important for activation of PIII have been identified in B and T cells (15,35,36,39). In addition, a region upstream of PIII responsible for CIITA expression in response to IFN-␥ has been identified and involves binding of STAT-1, but not IRF-1 (40).…”
Section: Discussionmentioning
confidence: 99%
“…Although constitutive CIITA expression is restricted to B lymphocytes and professional APCs, CIITA is also induced by the inflammatory cytokine IFN-␥ in most other cell types, including T cells (16,20,26,86). CIITA expression is also induced in activated human T cells (31)(32)(33). CIITA interacts with the constitutively expressed DNA-binding transcription factors RFX5, NF-Y, and CREB to assemble a B lymphocyte-specific enhanceosome that regulates MHC class II gene expression (22)(23)(24)(25)(26)86).…”
Section: Discussionmentioning
confidence: 99%